'Ihr Berge, adieu' – nature as a sanctuary for a persecuted Munich Jew. Issue 1 (2nd January 2020) - Seehuber, Katharina
ABSTRACT: The connectedness of place, space and time is a well-known idea in the context of space in social theory. This paper argues that the factor of agency, specifically the question whether meaning is given to a space in a conscious or unconscious process, should also be discussed. By analysing a body of correspondence, the perception of nature in the eyes of the Munich Jewish citizen, Erwin Schwager, during the Nazi period is explored, showing the meaning of nature as space of Heimat, recreation and sanctuary in changing circumstances. The usage of a microhistorical approach proved effective for linking the concepts of place, space, time and agency.